2009
DOI: 10.1063/1.3072719
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of various borides: The role of stretched c-parameter

Abstract: The superconductivity of MgB 2 , AlB 2 , NbB 2+x , and TaB 2+x is intercompared. The stretched c-lattice parameter ͑c = 3.52 Å͒ of MgB 2 in comparison to NbB 2.4 ͑c = 3.32 Å͒ and AlB 2 ͑c = 3.25 Å͒ decides empirically the population of their and bands and as a result their transition temperature T c values, respectively, at 39 and 9.5 K for the first two and no superconductivity for the later. The nonstoichiometry induces an increase in c parameter with Boron excess both in NbB 2+x and TaB 2+x . Magnetization … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…The μ 0 H c2 (0) is estimated to be ∼16.3 T, a surprisingly high upper critical field for this class of the material. 19 The fitting in Fig. 9 data allows an estimation of the coherence length through of the Ginzburg-Landau formula:…”
Section: Resultsmentioning
confidence: 99%
“…The μ 0 H c2 (0) is estimated to be ∼16.3 T, a surprisingly high upper critical field for this class of the material. 19 The fitting in Fig. 9 data allows an estimation of the coherence length through of the Ginzburg-Landau formula:…”
Section: Resultsmentioning
confidence: 99%
“…[343] Noting that MgB 2 possesses one of the longest c-axis among the diborides (3.52 Å) and the deleterious role of pressure on T c , Wan et al theoretically modeled various MgB 2 lattice parameters and found that stretching the c-axis and compressing the a-axis should raise the T c . Indeed, parallel experiments with NbB 2+x (T c = 9.4 K) [344] and MoB 2+x (T c = 7.5 K) [345] have shown that the addition of excess boron can help separate the boron layers and induce Adv. Mater.…”
Section: Figurementioning
confidence: 98%
“…However, the hope of finding other superconductors in the material class of the diborides with even higher T c was not fulfilled: The related isostructural stoichiometric compounds, for instance, AlB 2 , NbB 2 , TaB 2 , and ZrB 2 , do not superconduct. 3,4 Among the diborides MgB 2 seems to be an isolated sample of a superconductor with an exceptionally high T c in contrast to the recently synthesized iron pnictides 5 among them many superconductors derived from a nonsuperconducting parent compound exist. 6 Beside the quest for superconductivity in compounds of the same chemical family, chemical doping or alloying is a promising method to tune superconducting properties like T c , the critical current density j c in a magnetic field, and the upper critical field H c2 .…”
Section: Introductionmentioning
confidence: 97%